Influence of lupin and chickpea flours on acrylamide formation and quality characteristics of biscuits. (15th February 2023) - Schouten, Maria Alessia; Fryganas, Christos; Tappi, Silvia; Romani, Santina; Fogliano, Vincenzo
Graphical abstract: Highlights: Asparagine concentration was equalized in all biscuit formulas. The type of flour can strongly affect acrylamide formation in biscuits. Lupin flour was not effective in reducing acrylamide content in biscuits. Chickpea flour did not influence the texture and colour of the final biscuits. The use of chickpea flour is a promising strategy for acrylamide control in biscuits. Abstract: Asparagine and sugars are direct precursors of acrylamide; however, proteins and fibres can also influence it. In this study, biscuits prepared replacing wheat flour with increasing concentrations (20, 40, 60%) of lupin or chickpea flour were investigated. Asparagine concentration was equalized in all formulas to isolate the effect of other flour characteristics on the acrylamide formation during baking. The results showed that replacing wheat flour with lupin flour increased acrylamide from 583.9 up to 1443 µg/kg after 9 min of baking, while 20–40% chickpea flour reduced acrylamide to 354.4–312.6 µg/kg. The acrylamide reduction using chickpea was attributed to the lower interaction between precursors resulting from both the coarser particle size and the lower reactivity of carbohydrate in presence of chickpea proteins. Chickpea addition did not affect the colour and texture of biscuits, opening the possibility for large-scale implementation of this mitigation strategy in formulas with a similar initial asparagine content.